Empowering Housewives Through Education on the Dangers of Usury in Family Financial Management in Kwagean Village, Stalang - Firdaus Arjun; Nur Laili Hidayah; Shafrina Rizqi Jazilah; Suci Oktaviani; Icca Febita Prameswari; Afrida Widiyatni (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
Family financial management issues often pose a challenge for housewives, particularly when disputes arise over usury-based loans that promise convenience but have negative long-term impacts. This study aims to examine efforts to empower housewives through education about the dangers of usury as a preventative measure in managing family finances healthily and in accordance with Sharia values. The method used was a qualitative descriptive approach with a case study of the housewives' community in Kwagean Village. The study results indicate that providing education about usury can increase financial awareness, foster a critical attitude towards consumer credit offers, and encourage housewives to manage their finances wisely and independently. This education also strengthens the role of mothers as the primary regulators of the family economy and agents of change in their communities. Thus, empowerment based on religious values is one strategic solution in creating family economic resilience.